A Research Project on the Ecclesiastical Cartularies of Medieval Italy (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
Medieval European eclesiastical cartularies have been used for a long time only as historical sources, but nowadays the new research project Medieval European Cartularies (MECa) tries to study them as original works and to analyze their production and geographical distribution. the Italian research project called CartulIt, part of the MECa project, aims to draw up a catalog of Italian ecclesiastical cartularies.DOI 10.17464/9788867743353
Keywords: Ecclesiastical cartularies; manuscripts; Middle ages; Europe; Italy